PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, EFEKTIVITAS, DAN RISIKO PENGGUNAAN DIGITAL FUNDRAISING TERHADAP MINAT PEMBAYARAN DANA ZAKAT, INFAQ, DAN SHODAQOH (ZIS) PADA LEMBAGA ZAKAT - Fauzi Ilham Akbar; Burhan, M. Umar (Islamic Economics and finance in Focus, 2023)
The current economic condition of Indonesian society can be considered uneven. With the majority of the population being Muslims, the guidance and Islamic principles in addressing the problems of poverty within the community become important to implement. ZIS stands for Zakat, Infaq, and Shodaqoh, which refer to activities carried out by Muslims to share with those in need. In this digital era, people tend to transform their behaviors into digital lifestyles in every activity and transaction they engage in. This also extends to the community in terms of increasing the collection of ZIS funds. This study aims to determine the effects of the perceived ease of use, perceived effectiveness, and the perceived risk of digital fundraising usage on the intention to pay ZIS funds. The population of this research consists of the residents of Malang City who use digital fundraising to pay ZIS. A sample of 123 respondents was selected using purposive sampling technique. Data collection was conducted by distributing questionnaires to the respondents. The data were analyzed using Structural Equation Modeling with SmartPLS software. The results of the study indicate that the perceived ease of use significantly effect on the intention to pay ZIS using digital fundraising (online), the effectiveness variable significantly effect on the intention to pay ZIS using digital fundraising (online), and the risk variable does not significantly effect on the intention to pay ZIS using digital fundraising (online).